A Comparison of Reproductive Performances in Young and Old Females: A Case Study on the Atlantic Bluefin Tuna in the Mediterranean Sea - Luca Marisaldi; Orsola Iorillo; Danilo Basili; Giorgia Gioacchini; Julien Bobe; Violette Thermes; Francesca Maradonna; Oliana Carnevali (Animals, 2021)
In the Mediterranean Sea, a demographic substructure of the Atlantic bluefin tuna Thunnus thynnus has emerged over the last decade, with old and young individuals exhibiting different horizontal movements and spatial–temporal patterns of gonad maturation. In the present study, histology and molecular reproductive markers were integrated with the gonad-specific mir-202 gene expression and ovarian localization to provide a comprehensive picture of the reproductive performances in young and old females and investigate the role played by the mir-202 during gonadal maturation. During the reproductive period, old females (>100 kg; 194.6 ± 33.9 cm straight fork length; 11.3 ± 2.7 years old) were found to have greater reproductive performances than younger females (<80 kg; 139.3 ± 18.8 cm straight fork length; 8.4 ± 1.1 years old) according to gene expression results, suggesting a prolonged spawning season, earlier arrival on spawning grounds and/or better condition in older females. The mir-202-5p showed no global changes; it was abundantly expressed in granulosa cells and faintly present in the ooplasm. On the other hand, the mir-202-3p expression profile reflected levels of oocyte maturation molecular markers (star, lhr) and both histological and molecular (casp3) levels of follicular atresia. Overall, old females exhibited greater reproductive performances than younger females, likely reflecting different reproductive dynamics linked to the physical condition, habitat usage and migratory behaviour. These results highlight the importance of preserving large and old females in the context of fishery management. Finally, the mir-202 appears to be a good candidate to regulate the reproductive output of this species in an autocrine/paracrine manner through either stage- or age-dependent processes.